Detection of InvA Gene in Isolated Salmonella from Broilers by PCR Method - Salehi, T. Zahraei; Mahzounieh, M.; Saeedzadeh, A. (International Journal of Poultry Science, 2005)
The presence of Salmonella was detected in 192 samples of poultry carcasses from poultry farms in Shiraz province (Iran). A total of 30 Salmonella isolates were found in chicken samples (15.6%), by conventional culturing and confirmed by PCR and serology methods. Strains of serogroup D1 were the most prevalent strains, followed by serogroups C1, B and C2. All strains were subjected to Salmonella-specific gene (invA) and were confirmed as Salmonella positive by the predicted product a 284-bp DNA fragment.